Love Overcomes Fear and Brings Freedom: The Courage of the Female Characters in the Pentateuch - Avsenik Nabergoj, Irena (Studia Gdańskie, 2023)
Using the method of integrated literary analysis, the article examines comparatively the narratives of Genesis and Exodus, which in different ways explicitly or implicitly express the emotions of the female characters in a situation of trial. It emphasises the relationship between their fear and their courage, which leads them to experience the freedom to choose the ethical values of compassion, mercy and love. From these perspectives, the following texts are highlighted: the narrative of the conflict between Sarah and Hagar (Gen 16 and 21); the narrative of Isaac's marriage to Rebekah (Gen 24) and of Jacob's marriage to Leah and Rachel (Gen 29-30); and the narrative of Pharaoh's daughter's compassion for the Hebrew child Moses (Exod 1:8-2:10). The article emphasises the motif of motherhood and shows that the sense of motherhood brings wives and mothers from different cultural and religious backgrounds closer together in caring for their children and thus for the future of the family and the tribal community. In identifying the motives that influence female characters' decisions in trial, the article highlights the role of their religious sense as well as other personal and family circumstances and the expectations of the wider community.